AB0258 CAROTID INTIMA-MEDIA THICKNESS AND SERUM BIOMARKERS IN PARAGUAYAN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Valinotti, V.; Paats, A.; Acosta, R.; Roman, L.; Acosta-Colman, I.; Duarte, M.; Centurion, O.; Martinez, T.; De Abreu, P.; Avila, G.; Cabrera-Villalba, S.
Abstract : Background: The mechanism of increased cardiovascular risk in RA is not well understood and is independent of traditional CV risk factors. Intima-media thickness of the common carotid wall measured by ultrasonogram is a safe and useful biomarker of early stage atherosclerosis that correlates with coronary involvement; and it correlates with severity and duration of disease. Several studies have shown a relationship between inflammation markers, endothelial dysfunction markers, and carotid involvement. (1) Objectives: To determine the presence of inflammation biomarkers and its relationship with subclinical atherosclerosis measured by carotid ultrasound, and with the clinical characteristics in patients with established Rheumatoid Arthritis (RA) Methods: Descriptive, cross sectional, prospective study, in a Paraguayan cohort of patients with RA meeting ACR/EULAR2010 criteria. This study had two phases: the first one, included a standardized questionnaire according to the variables included in the Cardiovascular Risk project (PINV15-0346), from the National Sciences and Technology Council (CONACYT), and physical examination; the second one included laboratory sample collection performed by a specialized laboratory for serum biomarkers measurement for cardiovascular risk prediction (i.e endothelin, alpha-TNF, E-selectin, homocysteine, apolipoprotein, fibrinogen, and high sensitivity-CRP levels) and carotid ultrasound evaluation by a trained specialist, to evaluate subclinical atherosclerosis. Subclinical atherosclerosis was defined as carotid intima-media thickness (CIMT) >0, 9mm and/or presence of carotid plaques. All patients signed informed consent. SPSS 23rd version was used for data analysis. Quantitative variables were presented as means and qualitative as frequencies. Chi square test was performed for comparisons between dichotomous variables and t Student for continuous, and p ≤ 0.05 for statistical significance. Results: 100 patients were included, 87% were women, mean disease duration 130.9±102.64 months, 77% were RF positive, and 84.4% were ACPA positive, 43.4% had bone erosions, mean ESR-DAS28 was 3, 42±1, 1; 30% had remission criteria. 39% had extra-articular manifestations. Elevated serum biomarkers were found: fibrinogen >400 mg/dL 88.2%, high sensitivity-CRP (hs-CRP) >5mg/dL 42.9%, endothelin >2 ng/mL 20%, alpha-TNF >15, 6 pg/mL 13.1%, E-selectin >79, 2 ng/mL 6%. 25.3% had CIMT >0, 9 mm and mean CIMT was 0.68±0.25mm. 27.14% had carotid plaques. Patients with CIMT>1mm had higher frequency of family history of arterial hypertension (p=0.006), greater mean disease duration (p=0.0007), hip circumference (p=0.014), blood pressure (SBP p=0.038, DBP p=0.027), HAQ levels (p=0, 019) and hs-CRP levels (p=0.013), also lower mean height (p=0, 04); while carotid plaques were related to higher homocysteine (p=0.026) and hs-CRP levels (p=0.024). Conclusion: A considerable percentage of patients had subclinical atherosclerosis. Patients with CIMT>0, 9mm had a longer disease duration, higher HAQ levels, hip circumference, as well as higher BP. High levels of hs-CRP were more frequently related to the presence of subclinical atherosclerosis References: [1]Aday, A. targeting residual inflammatory risk: a shifting paradigm for atherosclerotic disease. Frontiers in cardiovascular medicine. 2019. 6:16. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6403155/pdf/fcvm-06-00016.pdf Disclosure of Interests: None declared